A RE-APPRAISAL OF AFRICAN TRADITIONAL RELIGIOUS PERSPECTIVE ON THE NIGERIAN COMMON WEALTH SYSTEM (American Journal of Research in Humanities and Social Sciences, 2025)
This article attempts to showcase how African traditional religious models can be utilized to resolve the overwhelming multifaceted problems of the Nigeria common wealth issues bothering on injustice, natural resources sharing, religious intolerance, political structure and its office sharing, animal rearing/husbandry, social welfare distribution, religio-cultural values, indiscipline and lawlessness, corruption, electoral processes and even boundary delineation, multi-lingual, multi-ethnic, multi-religious differences etc., which are all overwhelming, indices that all is not well with Nigeria as a nation. It adopted the descriptive approach as its methodology pointing out the shortfalls in this issue. The paper ends by pointing out the use of African traditional paradigm in the process of resolution and advocates for a way forward by using these mechanisms as its solutions.